Effects of different training schedules based on distance and accelerometry measures: A full-season case study in professional soccer players - Hadi Nobari; Nader Alijanpour; Amirhossein Talvari; Rafael Oliveira (Scientific Reports, 2023)
Abstract This study aimed to evaluate external load based on distance and accelerometry measures in six different microcycle schedules with congested (CW2, CW3, and CW4) and regular weeks (RW4, RW5, and RW6) in professional soccer players. Twelve Iranian First League players (age: 28.2 ± 3.8 years; body mass: 77.92 ± 4.72 kg, and height: 183.2 ± 0.06 cm) participated in this study. A GPSPORTS system was used to collect training/match durations, total distance, distance covered at different speeds, number of accelerations, delecelerations and body load over 29 weeks, 40 matches, and 121 training sessions. Data were analysed by weekly mean and accumulated weekly values. The results showed a tendency for higher values in CWs than RWs. Regarding mean total distance, RW4 and RW5 presented lower values with very large effect size than CW2 (all, p < 0.05). The mean distance covered between 16 and 23 km/h showed that all RWs presented significantly lower values than all CWs (p < 0.05 with considerable effect size). In addition, mean acceleration values at < 2 m/s2 showed significantly lower values than all CWs (p < 0.05 with a very large effect size). Therefore, it is recommended to coaches pay special attention to players who participate in matches to reduce fatigue and improve the performance of professional soccer players. Ensuring recovery mechanisms are in place to minimize the external load is recommended. Coaches arrange practice sessions for non-starters who do not experience similar external loads compared to starters to prepare them for potential competition.